2010
DOI: 10.1108/09675421011050009
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility

Abstract: PurposeThe purpose of this paper is to attempt to identify the type and quality of social information disclosed by Lebanese commercial banks and to report on the extent of these disclosures and their relationship with size, financial performance, and other chosen variables.Design/methodology/approachDeductive in nature, this paper uses content analysis of annual report social disclosures of 24 Lebanese commercial banks to test six hypotheses related to the nature of social disclosures and their association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…Table 3 presents the eight disclosures items related to human resources that used content analysis. The items were adopted from prior studies in the accounting literature for sample companies [34,[37][38][39][40][41][42][43]. First, based on literature review, human resources related disclosure items were identified.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 presents the eight disclosures items related to human resources that used content analysis. The items were adopted from prior studies in the accounting literature for sample companies [34,[37][38][39][40][41][42][43]. First, based on literature review, human resources related disclosure items were identified.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…Human resources disclosure in corporate annual reports was collected manually via content analysis. Eight categories were pre-defined to assess objectively human resources related information based on a review of accounting literatures [34,[37][38][39][40][41][42][43]. Disclosure related to employee health and safety, employment of minorities or women, disabled employee, employee training, employee assistance/benefits, employee remuneration, employee profiles and employee morale are defined as human related disclosures [34,[37][38][39][40][41][42][43].…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…Most of the studies of the banking industry document a positive link between these two constructs (e.g. [84], [42], [81], [65]). …”
Section: Research Goal and Hypothesesmentioning
confidence: 99%
“…[87], [14], [67], [88], [54]), and only some refers specifi cally to the banking industry (e.g. [81], [65]). …”
Section: Research Goal and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation